PENERAPAN MODEL KOMUNIKASI INTERPERSONAL TERHADAP PENYEMBUHAN PASIEN (STUDI PADA RUMAH SAKIT ISLAM METRO DAN RSU MUHAMMADIYAH METRO) - nurkholis nurkholis (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Care and healing patients in hospitals is not just a matter of medical care, more than that requires a holistic-comprehensive approach covering the spiritual aspects of patients. The importance of spiritual aspects in supporting the healing of patients cannot be negotiated anymore, because patients in hospitals, especially inpatients with acute illness not only suffer from various physical ailments but they also experience various stresses and spiritual mental disorders from mild to severe as the result of his illness. Patients who suffer from severe illness experience various anxieties, fears, as well as patients who will face surgery and post-surgery, patients who face critical moments such as facing death, dying, is not the realm of medical care issues alone, but it really needs assistance, services, and spiritual assistance. This study tries to apply a communication model carried out by spiritual guidance (Binroh) to patients in the Islamic Hospital and Muhammadiyah Metro Hospital. This research aims to determine the application of interpersonal communication models of spiritual guidance (binroh) at Islamic Hospital and Muhammadiyah Metro Hospital to the healing of patients, as well as the results achieved in the application of interpersonal communication in both hospitals. This research uses a qualitative approach. Terminologically qualitative research is research that produces descriptive data in the form of written or oral words from people or observable behavior. Qualitative research methods seek to understand and interpret the meaning of an event in human behavior interactions in certain situations. Researchers in this case make direct observations in the process of fostering patients by spiritual staff in Islamic Hospital and Muhammadiyah Metro Hospital.